Jupiter - Zobel, Derek, 1983- (Minneapolis, MN : Bellwether Media, 2010)
"Introductory text and full-color images explore the physical characteristics and discovery of Jupiter. Intended for students in kindergarten through third grade"--Provided by publisher.
Includes bibliographical references (p. 23) and index.
Keywords: Jupiter (Planet) -- Juvenile literature